Animasi Berbasis Konteks Situasi sebagai Metode Pembelajaran Jidoushi+Iru dan Tadoushi+Aru (Implementasi Penggunaan Hemisfer Kanan) - Winingsih, Irma; Wahyuningsih, Tri Mulyani (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
There are three suggestions regarding teaching techniques related to the hemispheres, namely: creating a learning environment, varied, and real educational experience, trying to help students overcome their fear of learning. challenging environments and condition students to combine information into their memories by processing it. Animation as learning media are that animated films can create a deep impression for teachers or students, the sounds and movements displayed are visualizations of reality, according to the material presented in the lesson. With interpretation techniques, animation become a medium that can then activate the right hemisphere function, especially for 6th semester students of the Japanese language study program at Dian Nuswantoro University regarding the use of verbal sentence patterns jidoushi+iru and tadoushi+aru which always appear every year as a discussion of Minnano's book. Nihongo II.The result is this animated video the author makes can meet the standard of visual animation as a learning medium